CHEVIE: a system for computing and processing generic character tables - Geck, Meinolf; Hiss, Gerhard; Lübeck, Frank; Malle, Gunter; Pfeiffer, Götz (Applicable algebra in engineering, communication and computing, 1996)
CHEVIE is a computer algebra package which collects data and programs for the representation theory of finite groups of Lie type and associated structures. We explain the theoretical and conceptual background of the various parts of CHEVIE and we show the usage of the system by means of explicit examples. More precisely, we have sections on Weyl groups and Iwahori-Hecke algebras, generic character tables of series of finite groups of Lie type, and cyclotomic algebras.